Upconversion and infrared emission of Er3+/Yb3+ co-doped SiO2-Gd2O3 obtained by sol-gel process - Rocha, Leonardo A.; Ribeiro, Sidney José L. [UNESP]; Pereira, Arnaldo C.; Schiavon, Marco A.; Ferrari, Jefferson L. (National Library of Serbia, 2015)
This work reports on the preparation of materials based on Yb3+/Er3+ co-doped SiO2-Gd2O3 via sol-gel process. The 0.4mol%of Er3+ ions was fixed and the amount of Yb3+ ions changed as 1.8, 5 and 9mol%in order to evaluate the photoluminescence properties as a function of the Yb3+ ions concentration. The prepared xerogels were heat-treated at 900, 1000 and 1100 °C for 8 h. X-ray diffraction analyses of the heat-treated materials confirmed the formation of the Gd2O3 cubic phase embedded in the SiO2 host, demonstrating the effective incorporation of RE3+ ions in the structure. The Scherrer's equation verified that the sizes of Gd2O3 nanocrystallite are between 31 and 69 nm and directly dependent on the heat-treatment temperature. Under excitation at 980 nm all materials showed upconversion phenomena, and the intensities of the emissions in the green and red regions showed to be directly dependent on power pump of laser, quantity of Yb3+ ions and heat-treatment temperature. The materials also showed emission in the infrared region with the maximum around 1530 nm, assigned to the transition of 4I13/2 → 4I15/2 of the Er3+ ions, region known as technological C-telecom band used in optical amplification.
Keywords: C-telecom window; Photoluminescence; Rare earths; SiO2-Gd2O3 ceramic